Study on the correlation between mobility and dispersion of different types of fibers in engineered cementitious composites (ECC) - Xiao Wang; Haowen Jing; Ruonan Deng; Bin Meng; Xiaolin Huo (Case Studies in Construction Materials)
In order to improve the crack resistance of traditional concrete, cement, silica fume, fly ash and quartz sand were used as the research objects. The dispersion of different types of fibers was characterized by Water washing method, Cross-sectional analysis method and Fluorescence analysis method. The effects of thickeners on the fluidity of matrix were studied by Truncated cone extension method, Marsh cone measurement method and Mortar consistency tester. The composite effects of fiber dispersion and matrix fluidity on the mechanical properties of Engineered Cementitious Composites (ECC) were investigated. The results show that the effect of fluidity on fiber dispersion is closely related to fiber density. When the thickener content is 0.3 ‰, the dispersion of basalt fiber and steel fiber is the best. When the thickener content is 0.1 ‰, the dispersion of PVA fiber is the best. The mechanical properties of ECC materials are affected by both fiber dispersion and porosity under the influence of fluidity.